NEW TECHNOLOGIES AND FINANCIAL EDUCATION - Darôs, Andréia Brognoli; da Rosa, Josimara Rodrigues (Revista Interface Tecnológica, 2023)
Technological innovations bring with them new challenges to the economic context, demanding new skills from citizens to live in this constantly changing scenario, while also providing many opportunities for access to knowledge. Thus, this work brings a bibliographical analysis on the New Technologies of Information and Communication and their contributions in the teaching-learning of financial education. The use of Serious Games, Artificial Intelligence, blockchain and Big Data and their contributions to the fields of education and economics were analyzed. From the literature found on the impacts of new technologies on the economy and education, it was identified that these resources contribute to the teaching-learning process of financial education. The economic scenario has undergone significant transformations and new technologies help prepare the population for digitalization of financial services through financial education and digital skills, both consisting of the conscious use of money and technology, respectively.